2019
DOI: 10.3390/agriculture9060114
|View full text |Cite
|
Sign up to set email alerts
|

Highly Porous and Nutrients-Rich Biochar Derived from Dairy Cattle Manure and Its Potential for Removal of Cationic Compound from Water

Abstract: The use of biochar in the horticulture and crop fields is a recent method to improve soil fertility due to its porous features and rich nutrients. In the present study, dairy manure (DM) was used as a biomass precursor in the preparation of highly porous biochar (DM-BC) produced at specific conditions. Based on N2 adsorption-desorption isotherms and scanning electron microscopy (SEM) observations, the resulting biochar featured its microporous/mesoporous textures with a BET surface area of about 300 m2/g and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 24 publications
(46 reference statements)
3
8
0
Order By: Relevance
“…The elongation (or better coverage of roots) in PLB-amended rhizosphere in our study supports an earlier mesocosm study that concluded that the addition of biochar (charcoal fines from mixed-deciduous wood in this case) to the rhizosphere effectively elongates the plant roots [64]. Addition of biochar to aridic calcareous soil very likely increases total pore volume [65], decreases bulk density [66], and enhances cation exchange capacity (CEC) of soil system [66]. The decreasing bulk density and increasing porosity, CEC, and nutrient holding capacity in response to increasing black carbon (or biochar) in soil were also verified in an x-ray absorption microscopic study [34,67].…”
Section: Discussionsupporting
confidence: 88%
“…The elongation (or better coverage of roots) in PLB-amended rhizosphere in our study supports an earlier mesocosm study that concluded that the addition of biochar (charcoal fines from mixed-deciduous wood in this case) to the rhizosphere effectively elongates the plant roots [64]. Addition of biochar to aridic calcareous soil very likely increases total pore volume [65], decreases bulk density [66], and enhances cation exchange capacity (CEC) of soil system [66]. The decreasing bulk density and increasing porosity, CEC, and nutrient holding capacity in response to increasing black carbon (or biochar) in soil were also verified in an x-ray absorption microscopic study [34,67].…”
Section: Discussionsupporting
confidence: 88%
“…The dairy manure (DM) for producing biochar was obtained from the livestock farm at the National Pingtung University of Science and Technology (Pingtung, Taiwan). Details on the DM pretreatment were described in the previous studies [21][22][23].…”
Section: Methodsmentioning
confidence: 99%
“…In this work, the thermochemical properties of DM, including proximate analysis, ultimate (elemental) analysis, calorific (heating) value, inorganic elements, and thermogravimetric analysis (TGA), were conducted to evaluate the potential for producing porous biochar at adequate pyrolysis conditions. Again, details on the thermochemical analysis of oven-dried DM were described previously [21][22][23].…”
Section: Thermochemical Analysis Of Oven-dried Dmmentioning
confidence: 99%
“…Among the carbonization conditions that influence the pore properties of biochar, the pyrolysis temperature could be the most important process parameter [24]. According to the results previously studied [15,25], the CPH-based biochar products (denoted as CPH-BC-400, CPH-BC-500, CPH-BC-600, CPH-BC-700 and CPH-BC-800) were produced under a nitrogen flow (500 cm 3 /min) atmosphere at the following carbonization conditions: temperatures of 400-800 • C, residence time of 30 min and heating rate of 10 • C/min. Using 10 g for each pyrolysis experiment, the yields of the CPH-based biochar products showed the values ranging from 40.70% at 400 • C to 30.22% at 800 • C. Subsequently, the biochar products (i.e., CPH-BC-400 and CPH-BC-800) were separately mixed with 0.25 M HCl (Merck Co., Darmstadt, Germany) solution (about 100 cm 3 ) on a hot-plate where the solution was heated to about 75 • C for 30 min.…”
Section: Pyrolysis and Post-acid Treatment Experimentsmentioning
confidence: 99%
“…Referring to the previous study [25], the adsorption kinetics of the optimal biochar (i.e., CPH-BC-800-AW) was preliminarily tested in an agitating tank for the removal of methylene blue (MB) from 2 L of aqueous solution. The adsorption conditions were fixed at the solution temperature of 25 • C biochar dosage of 0.3 g and agitation speed of 200 rpm, but changed in the initial MB concentrations (i.e., C o = 5, 10, and 15 mg/L).…”
Section: Adsorption Experimentsmentioning
confidence: 99%